Effect of exercise alone and in combination with time-restricted eating on cardiometabolic health in menopausal women - Beata Jóźwiak; Remigiusz Domin; Monika Krzywicka; Ida Laudańska-Krzemińska (Journal of Translational Medicine)
Abstract There is a need to investigate the effect of lifestyle modifications on cardiometabolic health-related issues that occur during menopause. The aim of this study was to compare the effect of resistance and endurance circuit training program alone (exercise group, n = 34) with the effect of time-restricted eating (16:8) combined with a training program (combination group, n = 28) on cardiometabolic health in 62 menopausal women (aged 51.3 ± 4.69 years). Testing was conducted before and after a 12-week period and included an assessment of body composition, glycemic control, lipid panel, blood pressure, and anthropometric measurements. Decreases in body mass index and systolic blood pressure were significantly greater in the combination group than in the exercise group (F(1,60) = 4.482, p = 0.038, η2 = 0.07; F(1,57) = 5.215, p = 0.026, η2 = 0.08, respectively, indicating moderate effects). There were significant decreases in fat mass (p = 0.001, r = 0.654), glucose level (p = 0.017, r = 0.459), insulin level (p = 0.013, r = 0.467), homeostatic model assessment for insulin resistance (p = 0.009, r = 0.499), waist circumference (p = 0.002, r = 0.596), and waist-to-height ratio (p = 0.003, r = 0.588) (indicating moderate effect) in the combination group, while there were no significant changes in the exercise group. There were no changes in lipid panel indicators in either group. This is the first study to investigate the effect of time-restricted eating combined with exercise in menopausal women. The results of the study provide evidence that the combination of time-restricted eating and exercise leads to a greater body mass index reduction than exercise alone in menopausal women. Trial registration: ClinicalTrials.gov, NCT06138015 registered 18 November 2023—Retrospectively registered, https://clinicaltrials.gov/study/NCT06138015 .